Monitoring of air pollution levels related to Charilaos Trikoupis Bridge - Sarigiannis, D.; Handakas, Evangelos J.; Kermenidou, Marianthi V.; Zarkadas, Ioannis S.; Gotti, Alberto; Charisiadis, Pantelis; Makris, Konstantinos C.; Manousakas, Manousos Ioannis; Eleftheriadis, Konstantinos; Karakitsios, Spyros P. (My University, 2017)
Charilaos Trikoupis bridge is the longest cable bridge in Europe that connects Western Greece with the rest of the country. In this study, six air pollution monitoring campaigns (including major regulated air pollutants) were carried out from 2013 to 2015 at both sides of the bridge, located in the urban areas of Rio and Antirrio respectively. Pollution data were statistically analyzed and air quality was characterized using US and European air quality indices. From the overall campaign, it was found that air pollution levels were below the respective regulatory thresholds, but once at the site of Antirrio (26.4 and 52.2 μg/m 3 for PM 2.5 and ΡΜ 10 , respectively) during the 2nd winter period. Daily average PM 10 and PM 2.5 levels from two monitoring sites were well correlated to gaseous pollutant (CO, NO, NO 2 , NO x and SO 2 ) levels, meteorological parameters and factor scores from Positive Matrix Factorization during the 3-year period. Moreover, the elemental composition of PM 10 and PM 2.5 was used for source apportionment. That analysis revealed that major emission sources were sulfates, mineral dust, biomass burning, sea salt, traffic and shipping emissions for PM 10 and PM 2.5 , for both Rio and Antirrio. Seasonal variation indicates that sulfates, mineral dust and traffic emissions increased during the warm season of the year, while biomass burning become the dominant during the cold season. Overall, the contribution of the Charilaos Trikoupis bridge to the vicinity air pollution is very low. This is the result of the relatively low daily traffic volume (~ 10,000 vehicles per day), the respective traffic fleet composition (~ 81% of the traffic fleet are private vehicles) and the speed limit (80 km/h) which does not favor traffic emissions. In addition, the strong and frequent winds further contribute to the rapid dispersion of the emitted pollutants.
Keywords: Air quality indices; Air quality monitoring; Cable bridge; PM source apportionment